2010
DOI: 10.1111/j.1365-3156.2010.02526.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of methylene blue monotherapy in semi-immune adults with uncomplicated falciparum malaria: a controlled trial in Burkina Faso

Abstract: Summaryobjective To assess the efficacy of methylene blue (MB) monotherapy in semi-immune adults with uncomplicated malaria in Burkina Faso.methods In an open-label controlled phase II study with 60 semi-immune adults with uncomplicated falciparum malaria in Nouna, north-western Burkina Faso, MB monotherapy (390 mg twice daily) was given sequentially to groups of 20 adults for 7 days (MB7), 5 days (MB5) and 3 days (MB3), respectively. The primary outcome was the rate of adequate clinical and parasitological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…One recent field trial from Burkina Faso observed excellent clinical efficacy of a MB-amodiaquine combination when tested in children with uncomplicated falciparum malaria (34). Another study reported moderate curative activity with MB monotherapy, illustrating the need for this slow-acting drug to be combined with fast-acting agents (35). Our results show that MB interferes with gametocyte development at all stages and can block transmission through the potent clearance of stage V gametocytes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…One recent field trial from Burkina Faso observed excellent clinical efficacy of a MB-amodiaquine combination when tested in children with uncomplicated falciparum malaria (34). Another study reported moderate curative activity with MB monotherapy, illustrating the need for this slow-acting drug to be combined with fast-acting agents (35). Our results show that MB interferes with gametocyte development at all stages and can block transmission through the potent clearance of stage V gametocytes.…”
Section: Discussionmentioning
confidence: 73%
“…Characterized by a short plasma half-life and a high bioavailability (18 h and 72%, respectively) (30), this compound was the first synthetic compound ever used in clinical therapy, dating back to the 1891 report of its antimalarial properties by the renowned chemist Paul Ehrlich (31,32). Recently, there has been renewed interest in this affordable and already clinically registered compound, with a series of studies that have assessed the benefit of adding MB to antimalarial combinations (33)(34)(35). One recent field trial from Burkina Faso observed excellent clinical efficacy of a MB-amodiaquine combination when tested in children with uncomplicated falciparum malaria (34).…”
Section: Discussionmentioning
confidence: 99%
“…PRN has also been proven potent in vitro against P. falciparum isolates from Southeast Asia, a known area of multidrug resistance (23). Interestingly, PRN is also active against Plasmodium vivax in vitro (23), and recently, the in vivo efficacy of PRN-ART against P. vivax has been shown, making this combination a potential drug for the treatment of P. vivax infection as well (18).MB has proven efficacious in African countries, mainly in Burkina Faso (3,10,11,32), and has gametocytocidal properties; thus, it could be part of treatment combinations to reduce transmission of P. falciparum (6). Our data show that MB is active in vitro, in line with 2 previous studies using African parasites (1, 17).…”
mentioning
confidence: 99%
“…MB has proven efficacious in African countries, mainly in Burkina Faso (3,10,11,32), and has gametocytocidal properties; thus, it could be part of treatment combinations to reduce transmission of P. falciparum (6). Our data show that MB is active in vitro, in line with 2 previous studies using African parasites (1,17).…”
mentioning
confidence: 99%
“…Managing the unusual side-effect is possible via effective counselling of the patient, relatives etc. This has been achieved in recent years during the conventional use of methylene blue in juvenile malaria in Burkina Faso [5]. …”
mentioning
confidence: 99%